2021
DOI: 10.3390/ma14154148
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Design and Fabrication of Nanocomposites for Electromagnetic Wave Shielding and Absorbing

Abstract: Electromagnetic (EM) pollution has raised significant concerns to human health with the rapid development of electronic devices and wireless information technologies, and created adverse effects on the normal operation of the sensitive electronic apparatus. Notably, the EM absorbers with either dielectric loss or magnetic loss can hardly perform efficient absorption, which thereby limits their applications in the coming 5G era. In such a context, the hotspot materials reported recently, such as graphene, MXene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 153 publications
(208 reference statements)
0
21
0
Order By: Relevance
“…PANIcoated CNT on fabrics, 232 and MWCNT/PPy/chrome-tanned collagen ber (CF) 233 also exhibited enhanced electromagnetic interference performance. [234][235][236] Table 4 describes the preparative methods, thickness, frequency range and shielding performances for ICP/MWCNT, ICP/graphene and ICP-based ternary nanocomposites.…”
Section: Inherently Conducting Polymer Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…PANIcoated CNT on fabrics, 232 and MWCNT/PPy/chrome-tanned collagen ber (CF) 233 also exhibited enhanced electromagnetic interference performance. [234][235][236] Table 4 describes the preparative methods, thickness, frequency range and shielding performances for ICP/MWCNT, ICP/graphene and ICP-based ternary nanocomposites.…”
Section: Inherently Conducting Polymer Nanocompositesmentioning
confidence: 99%
“…The formation of binary nanocomposites comprising carbonaceous nanofiller intrinsically conducting polymers (ICPs) has been receiving considerable attention in EMI shielding applications. 214–275 This is mainly ascribed to the low density, ease of processability, tuneable electrical conductivity and environmental stability of ICPs. Recently, binary, ternary and quaternary nanocomposites have been receiving more attention for their microwave absorption properties.…”
Section: Inherently Conducting Polymer Nanocompositesmentioning
confidence: 99%
“…Ji et al reported that the carbon with increased sp2 hybridization delivers enhanced conductivity and finally improved electromagnetic absorption ability . As exhibited by Xie et al, the irregular cross sections of carbon fibers can promote multiple reflections inside the absorbing body, facilitating EWA performance . Zhang et al found that the dipolar loss of CNTs, ascribed to the electric rotation, can significantly optimize the dielectric loss .…”
Section: Introductionmentioning
confidence: 99%
“…Metallic oxides, such as NiCo 2 O 4 [ 20 ], Mn 3 O 4 [ 21 ], CuCo 2 O 4 -CuO composites [ 22 ], and Co 1.29 Ni 1.71 O 4 [ 8 ], have good magnetic loss characteristics, thus considered as excellent candidates for EMWAMs. However, carbon materials and conductive polymers have the disadvantages of impedance mismatching and narrow effective absorption bandwidth, and metal oxides suffer from gravimetric density and poor corrosion resistance [ 23 ]. To overcome these problems and broaden the application range of EMWAMs, diatomite, a biomimetic material with a unique 3D structure, has been noticed.…”
Section: Introductionmentioning
confidence: 99%